Redescription of the nematode Philometra obturans (Prenant, 1886) with a key to the philometrid nematodes parasitic in European freshwater fishes - Moravec, F (Folia parasitologica, 1978)
A redescription of the nematode Ph. obturans (Prenant, 1886), based on specimens from pike (Esox lucius L.) from the R. Elbe basin in Czechoslovakia, is presented. In addition to gravid, subgravid and mature females from the blood system also the male and mature female, found for the first time in the host's eye, are described. The paper is supplemented by a key for the identification of the philometrid nematodes parasitizing freshwater fishes of Europe.
Keywords: Československo; ryby; hlístice; Nematoda; ekologie; Ecology; Animals; Fishes; zvířata; Czechoslovakia